CONFLICT RESOLUTION STRATEGIES AS CORRELATE OF ADMINISTRATIVE EFFECTIVENESS IN PUBLIC COLLEGES OF EDUCATION IN KWARA STATE - ISIAKA, Gafar; IBRAHIM, Barakat; ZUHUMBEN, Beatrice, P. (Journal of Professional Counselling, 2025)
This study examined the relationship between conflict resolution strategies and administrative effectiveness in public colleges of education in Kwara State, Nigeria. A random sample of 180 respondents from public colleges of education in Kwara State participated in the study. The research design employed a questionnaire with two sections to gather data, which was analyzed using Pearson Product Moment Correlation. The study's findings revealed that effective conflict resolution strategies are essential for successful administration in colleges of education. The results showed that management styles of administrators are a primary cause of conflict, and effective conflict management is crucial for positive administrative outcomes. Based on the findings, the study recommends that college administrators should develop expertise in various conflict resolution strategies and consider individual differences among staff members to manage conflicts effectively. Additionally, the study suggests that colleges engage professional counsellors to help individuals or groups understand their goals, actions, and outcomes, promoting effective conflict resolution and administrative outcomes.